The effect of silica fume on properties of porous concrete paving block [electronic resource] - Ng, Mervyn Jingrong, 1990- author; Hasanan Md. Nor supervisor; Fakulti Kejuruteraan Awam (2014)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2014